Hydrodynamic Performance Analysis of Vertical Axis Water Turbine (VAWT) Gorlov Type With Hydrofoil Thickness and Inclination Angle Variables using Computational Fluid Dynamics (CFD) Approaches - Wardhana, Wisnu; Rahmawati, Shade; Satrio, Dendy; Nurliana, Annisa (Pusat Publikasi Ilmiah Institut Teknologi Sepuluh Nopember, 2022)
The issue of renewable and eco-friendly energy has become the focus of research in several countries to encourage eco-friendly alternative energy. One of them is by using turbines to produce electrical energy. Vertical Axis Water Turbine (VAWT) can be an exciting research object because it has various advantages. VAWT has a simpler structure, can move at relatively slow currents and is famous for its tendency to move regardless of the water flowdirections. In this study, the experimental turbine from secondary data numerically simulates using the Computational Fluid Dynamics (CFD) method with the help of ANSYS V18.1 software. The Gorlov turbine model is manufactured in 3 dimensions under steady-state flow conditions. Validation is carried out after obtained numerical results with the mean error rate being less than 10%. The variables in this research are the thickness of hydrofoil using NACA 0010, NACA 0016, NACA 0020, and variations in inclination angle of the blade for 25. After comparing the simulation results in the form of torque values is done, it is shown that the best turbine performance is given by water turbine using NACA 0016 with 60 and 60 of inclination angle.